PEMBERDAYAAN MASYARAKAT MELALUI KERAJINAN KANDANG AYAM DI DESA LAMPAR, TAMANSARI, BOYOLALI - SHOLEH ROHMADI; MARGARETHA PRABA AULIA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Lampar Village has abundant natural potential for bamboo. Until now, the use of bamboo has not been maximized both in terms of quantity and quality, even though bamboo can be used as a variety of crafts. Based on this, Lampar Village was chosen as the location for implementing KKN. The method carried out is in the form of training, with the following stages: (1) the preparation stage, (2) the implementation stage of the process and (3) the independence stage. The implementation of this Community Service activity was carried out on February 20 - March 31, 2021, namely in the form of activities: education and training for chicken coop handicrafts made from bamboo. The purpose of implementing KKN, namely: to provide knowledge to the community in utilizing natural resources around it to be used as crafts in an effort towards a prosperous community and an independent village. The results obtained were that the training activities went well and the participants followed the training activities until they were finished. The training was conducted interactively between the resource persons and the training participants.